2019
DOI: 10.1111/jnc.14658
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptors modulate the reorganization of F‐actin in Bergmann glia cells through the activation of RhoA

Abstract: Alpha‐amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionic acid glutamate receptors have been shown to modulate the morphology of the lamelar processes of Bergmann glia cells in the molecular layer of the cerebellum. Here we suggest that reorganization of F‐actin may underlay the changes in the morphology of the lamelar processes. Using the fluorescent staining of F‐actin with Phalloidin and the quantification of RhoA activation through immunoprecipitation or pull‐down assays, we show that RhoA is activated after sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…RhoA is a small G-protein in the Rho family. Studies have shown that it can regulate tight junction protein expression by modulating Claudin-2 expression [82] and actin [83,84], as shown in Figure 1.…”
Section: Effect Of Nitric Oxide On Intestinal Epithelial Tight Junmentioning
confidence: 99%
“…RhoA is a small G-protein in the Rho family. Studies have shown that it can regulate tight junction protein expression by modulating Claudin-2 expression [82] and actin [83,84], as shown in Figure 1.…”
Section: Effect Of Nitric Oxide On Intestinal Epithelial Tight Junmentioning
confidence: 99%